The impact of advertisements: how female magazine readers in China perceive fashion magazine advertisements and white skin - Wang, Kaidi (Kansas State University, 2017)
Most of the models in Chinese fashion magazine advertisements are Caucasian women today. White skin, as one of their Caucasian characteristics, is particularly emphasized. Millions of Chinese women are bombarded with the advertising’s message of “having white skin is beautiful” every day. My research suggests that this kind of adverting depicts white skin as a beauty ideal; the prevalence of Caucasian models in whitening products’ magazine advertisements constructs body-esteem, self-esteem, and purchase decision-making of Chinese women. The Social Judgment Theory is employed in this research as a theoretical framework. It is a way to explain when persuasive messages are most likely to succeed and how people make judgments about them. Understanding this phenomenon will ultimately provide insight into addressing the effects of the promotion of fashion magazine advertisements on Chinese women. It is further anticipated that future researchers will expand and improve the knowledge of the Chinese advertising market.
Keywords: Body esteem; Self esteem; Social Judgment Theory; Impact of advertisements; Chinese advertising market; Magazine advertisements